Tinkering With The ζ \zeta Function

Calculus Level 5

n = 1 ( ζ ( 2 n ) n 1 2 n 1 2 n + 1 ) \large \sum_{n=1}^{\infty} \left(\dfrac{\zeta(2n)}{n} - \dfrac{1}{2n} - \dfrac{1}{2n+1} \right)

Find the value of the closed form of the above series.

Give your answer to 1 decimal place.

Notation : ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ariel Gershon
Sep 22, 2016

n = 1 ζ ( 2 n ) 1 n = n = 1 1 n k = 2 1 k 2 n = k = 2 n = 1 1 n ( 1 k 2 ) n = k = 2 ln ( 1 1 k 2 ) = k = 2 ln ( k 2 ( k 1 ) ( k + 1 ) ) = lim m ln ( k = 2 m k 2 ( k 1 ) ( k + 1 ) ) = lim m ln ( 2 m m + 1 ) n = 1 ζ ( 2 n ) 1 n = ln ( 2 ) [ A ] \begin{array}{lllc} \displaystyle\sum_{n=1}^{\infty} \dfrac{\zeta(2n)-1}{n} & = & \displaystyle\sum_{n=1}^{\infty} \dfrac{1}{n}\displaystyle\sum_{k=2}^{\infty} \dfrac{1}{ k^{2n}} & \\ & = & \displaystyle\sum_{k=2}^{\infty} \displaystyle\sum_{n=1}^{\infty} \dfrac{1}{n}\left(\dfrac{1}{k^2} \right)^n & \\ & = & \displaystyle\sum_{k=2}^{\infty} -\ln\left(1 - \dfrac{1}{k^2}\right) & \\ & = & \displaystyle\sum_{k=2}^{\infty} \ln\left(\dfrac{k^2}{(k-1)(k+1)}\right) & \\ & = & \displaystyle\lim_{m\to\infty} \ln\left(\displaystyle\prod_{k=2}^{m} \dfrac{k^2}{(k-1)(k+1)} \right) & \\ & = & \displaystyle\lim_{m\to\infty} \ln\left(\dfrac{2m}{m+1} \right) & \\ \displaystyle\sum_{n=1}^{\infty} \dfrac{\zeta(2n)-1}{n} & = & \ln(2) & [A] \end{array}

On the other hand,

n = 1 ( 1 2 n 1 2 n + 1 ) = m = 2 ( 1 ) m m = 1 m = 1 ( 1 ) m + 1 m = 1 ln ( 2 ) [ B ] \begin{array}{lllc} \displaystyle\sum_{n=1}^{\infty} \left(\dfrac{1}{2n} - \dfrac{1}{2n+1} \right) & = & \displaystyle\sum_{m=2}^{\infty} \dfrac{(-1)^m}{m} & \\ & = & 1 - \displaystyle\sum_{m=1}^{\infty} \dfrac{(-1)^{m+1}}{m} & \\ & = & 1 - \ln(2) & [B] \end{array}

Therefore, adding equations ( A ) (A) and ( B ) (B) gives us:

n = 1 ( ζ ( 2 n ) n 1 2 n 1 2 n + 1 ) = 1 \displaystyle\sum_{n=1}^{\infty} \left( \dfrac{\zeta(2n)}{n} - \dfrac{1}{2n} - \dfrac{1}{2n+1} \right) = \boxed{1}

Normal standard approach +2

Ronny Fahrion - 4 years, 8 months ago

SInce, k = 2 ζ ( k ) x k 1 = ψ ( 1 x ) γ \displaystyle \sum_{k=2}^{\infty} \zeta(k)x^{k-1}=-\psi(1-x)-\gamma so we can derive k = 1 ζ ( 2 k ) x 2 k 1 = 1 2 ( ψ ( 1 + x ) ψ ( 1 x ) ) \displaystyle \sum_{k=1}^{\infty}\zeta(2k)x^{2k-1} = \frac{1}{2}(\psi(1+x)-\psi(1-x)) , Set x 2 x x^2\to x and divide throughout by x x ,

k = 1 ζ ( 2 k ) x k 1 = 1 2 x ( ψ ( 1 + x ) ψ ( 1 x ) ) \displaystyle \sum_{k=1}\zeta(2k)x^{k-1}=\frac{1}{2\sqrt{x}}(\psi(1+\sqrt{x})-\psi(1-\sqrt{x}))

Since, 1 2 n = 0 1 x 2 n 1 d x , 1 2 n + 1 = 0 1 x 2 n d x \displaystyle \frac{1}{2n}=\int_{0}^{1} x^{2n-1}dx,\frac{1}{2n+1}=\int_{0}^{1} x^{2n}dx and summing this the desired sum in integral representaion would be , S = 0 1 ψ ( 1 + x ) ψ ( 1 x ) + 1 1 1 x d x \displaystyle S=\int_{0}^{1} \psi(1+x)-\psi(1-x)+1-\frac{1}{1-x} dx

Now 0 1 ψ ( 1 + x ) d x = [ ln Γ ( 1 + x ) ] 0 1 = 0 \displaystyle\int_{0}^{1} \psi(1+x)dx = [\ln\Gamma(1+x)]_{0}^{1} =0 , 0 1 ( ψ ( 1 x ) + 1 1 x ) d x = [ ln ( Γ ( 1 x ) ( 1 x ) ) ] 0 1 = 0 \displaystyle \int_{0}^{1} (\psi(1-x)+\frac{1}{1-x})dx = [\ln(\Gamma(1-x)(1-x))]_{0}^{1}=0 as lim x 1 ( 1 x ) Γ ( 1 x ) = 1 \displaystyle \lim_{x\to 1} (1-x)\Gamma(1-x)=1

We are only left with S = 1 \displaystyle S= \boxed{1}

When you set x 2 x x^2 \to x , why doesn't x x become x \sqrt{x} in the arguments of ψ \psi ? i.e. It should be: k = 1 ζ ( 2 k ) x k 1 = 1 2 x ( ψ ( 1 + x ) ψ ( 1 x ) ) \sum_{k=1}^{\infty} \zeta(2k)x^{k-1} = \dfrac{1}{2\sqrt{x}}(\psi(1+\sqrt{x}) - \psi(1-\sqrt{x}))

Ariel Gershon - 4 years, 8 months ago

Log in to reply

Thanks for pointing out, was a typo

Aditya Narayan Sharma - 4 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...